Effects of the vibratory platform on balance, electromyographic activity and proprioception of the elderly (Research, Society and Development, 2021)
This study aimed to compare the effects of a physical-motor training in the elderly, on a vibratory platform and on the ground. Participants were three elderly, of both genders, between 61 and 66 years old. Patient 1 underwent sensortory-motor training on the vibratory platform and patients 2 and 3 on the ground. They were evaluated before, after one day and after five days of treatment. Patients 1 and 2 had improved balance after one day of treatment. After five days, only patient 1 showed improvement. Patient 3 improved after one day of treatment, which was maintained after five days. Patient 1 showed increased electrical activity of all muscles evaluated. Patient 2 showed increased electrical activity of the long fibular, vastus medial and gluteus media. The medial gastrocnemius muscle increased only after five days. There was an increase in the electrical activity of the vastus medial muscle of patient 3 in all evaluations. The middle gluteus increased only after five days. At the 60° angle of knee extension, patients 1 and 2 showed improvement of proprioception only after five days. No ângulo de 30°, a paciente 1 teve melhora após um dia e após os cinco dias, enquanto o paciente 2 apresentou melhora somente após o fim do tratamento. A paciente 3 teve melhora em todas as avaliações para 60° e 30° de extensão do joelho. Verificou-se que ambos os tratamentos foram benéficos para os idosos.